Short-Term Daily Prediction of Sea Ice Concentration Based on Deep Learning of Gradient Loss Function - Liu, Quanhong; Zhang, Ren; Wang, Yangjun; Yan, Hengqian; Hong, Mei (Frontiers in Marine Science, 2021)
The navigability potential of the Northeast Passage has gradually emerged with the melting of Arctic sea ice. For the purpose of navigation safety in the Arctic area, a reliable daily sea ice concentration (SIC) prediction result is required. As the mature application of deep learning technique in short-term prediction of other fields (atmosphere, ocean, hurricane, etc), a new model was proposed for daily SIC prediction by selecting multiple factors, adopting gradient loss function (Grad-loss) and incorporating an improved predictive recurrent neural network (PredRNN++). Three control experiments are designed to test the impact of these three improvements for model performance with multiple indicators. Results show that the proposed model has best prediction skill in our experiments by taking physical process and local SIC variation into consideration, which can continuously predict daily SIC for up to nine days.